2016
DOI: 10.3329/seajph.v6i1.30341
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice on hepatitis-B infection among infected patients in a Homoeopathy Medical Center in Dhaka City, Bangladesh

Abstract: Viral hepatitis is the commonest liver disease in Bangladesh. About 10 million people in Bangladesh have been suffering from hepatitis B. Hepatitis B is a potentiality life threatening liver infection caused by HBV. It is a major global health problem and the most serious type of viral hepatitis. The aim of this study is to assess the knowledge, attitude and practice on Hepatitis B Virus infection among the selected patients in Essence Homoeopathy Medical Center, Dhaka. A descriptive type of cross sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…We additionally assessed the personal hygiene characteristics. Overall our discoveries are predictable with previous reviews that have recorded learning and practices of cleanliness among school youngsters in developing nations [17].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…We additionally assessed the personal hygiene characteristics. Overall our discoveries are predictable with previous reviews that have recorded learning and practices of cleanliness among school youngsters in developing nations [17].…”
Section: Discussionsupporting
confidence: 65%
“…Remarkably, the self-reported incidence of hand washing before meals among undergraduates in our research is generously higher than frequencies announced from surveys of youths in comparison to the other countries. For example, students from Bangladesh showed that 75.9% and 46.9% of students revealed washing hands before suppers [17].…”
Section: Discussionmentioning
confidence: 99%
“…In the same line, recent studies showed low level of practice among studied participants regarding being screened or vaccinated. [8,10,18] In conclusion, the level of KAP toward hepatitis B was good in 56% of subjects with high scores of good knowledge and attitude but with poor practice levels among most of subjects.…”
Section: World Journal Of Pharmaceutical Researchmentioning
confidence: 80%
“…[5,6] The incidence of HBV infection is very high among hospital workers as most of them were never vaccinated. [7] The surveys that concern assessing the knowledge, attitude, and practice (KAP) toward hepatitis B could be used for improving the health and preventing the spread of infection, [8,10] This study was intended to study the KAP of Saudi population toward hepatitis B infection for providing good preventive measures.…”
Section: Introductionmentioning
confidence: 99%
“…The only predictor of vaccination uptake was being healthcare worker. Comparatively, in another study, 70% of the respondents did not have vaccination and it was proportionally linked to educational level [23].…”
Section: Discussionmentioning
confidence: 87%